Managerial accounting - Garrison, Ray H.; Noreen, Eric W.; Brewer, Peter C. (New York MCGraw Hill, 2021)
"For centuries, the lighthouse has provided guidance and safe passage for sailors. Similarly, Garrison/Noreen/Brewer has successfully guided millions of students through managerial accounting, lighting the way and helping them sail smoothly through the course"--
Includes index.
Keywords: Managerial accounting